THE MUSABAQAH HIFZHIL HADIS STQHN IN SOFIFI NORTH MALUKU 2021: Discourse on Hadith Pribumization in Millennial Generation - Falah, Mujahid Jamalul; Nurjanah, Zumrotus Sholikatun (Nabawi: Journal of Hadith Studies, 2025)
This research focuses on the Musabaqah Hifdzil Hadis in the XXVI STQHN performance in Sofifi, North Maluku 2021. This paper is based on two main issues of study, namely on the material of the musabaqah script and its impact on the indigenization of hadith. The background of this research includes the challenges of modernization in conveying the message of the prophetic spirit as well as the lack of public enthusiasm for hadith studies, especially since the opening of this study program separately in the State Islamic Religious Universities (PTKIN). This problem underscores the need for innovation and personalization in hadith studies to remain relevant and attractive to the millennial generation. The research method used is a qualitative approach with the technique of analyzing the texts of the participants of the Musabaqah Hifdzil Hadis. The results showed that although there is a significant spirit of learning in the study of hadith, efforts to personalize hadith for the millennial generation in Indonesia still need more attention. This study recommends the development of a variety of new formulations in the competition such as Qirā'ah al-ḥadīth min al-kutub al-mu'tabaroh, Understand Hadith, and Scientific paper of hadith to increase the relevance and impact of hadith studies in society. [Penelitian ini berfokus pada Musabaqah Ḥifẓ al-Ḥadīṡ dalam pagelaran STQHN XXVI di Sofifi, Maluku Utara 2021. Tulisan ini didasari pada dua persoalan utama kajian, yaitu pada materi naskah musabaqah serta dampaknya pada pribumisasi hadis. Latar belakang penelitian ini mencakup tantangan modernisasi dalam menyampaikan pesan ruh kenabian, serta masih minimnya semangat masyarakat terhadap kajian hadis terutama sejak dibukanya program studi ini secara terpisah di lingkungan Perguruan Tinggi Keagamaan Islam Negeri (PTKIN). Masalah ini menggarisbawahi perlunya inovasi dan pribumisasi dalam kajian hadis agar tetap relevan dan menarik bagi generasi milenial. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan teknik analisis teks naskah peserta Musabaqah Ḥifẓ al-Ḥadīṡ. Hasil penelitian menunjukkan bahwa meskipun ada semangat belajar yang signifikan dalam kajian hadis, upaya pribumisasi hadis pada generasi milenial di Indonesia masih memerlukan perhatian lebih. Penelitian ini merekomendasikan pengembangan ragam formulasi baru dalam musabaqah seperti qirā’ah al-ḥadīṡ min al-kutub al-mu’tabarah, fahm al-ḥadīṡ, dan Musabaqah Makalah Hadis (MMH) untuk meningkatkan relevansi dan dampak kajian hadis di masyarakat.]